Anatomia uczuć w przekładzie. Strategie tłumacza w oddawaniu warstwy emocjonalnej tekstu literackiego na przykładzie powieści Partygirl Marlene Streeruwitz - Bukowska, Joanna (Investigationes Linguisticae, 2019)
The focus of this article is an examination of translator’s dilemmas related to the rendering of emotions in the translation process. he relationship between emotions and the translation process is analyzed on the example of the novel Partygirl Marlene Streeruwitz and its Polish translation by Emilia Bielicka. The study focuses on the problem of translating emotional elements that are present in the source text and sheds light on how emotions can be translated. The article provides an introduction to the author's context which is of significance in understanding the role of emotions in the source text. The study shows how the Austrian writer conceives language and uses stylistic means and writing techniques to incorporate emotions into language structures. The analytical part consists of fragments of the novel that emphasize the emotional states of the main character and is devoted to the exploration of the lexical, syntactic and stylistic features. The undertaken analysis reveals the translator’s strategies and examines his decisions.